2016
DOI: 10.4103/0970-9371.182530
|View full text |Cite
|
Sign up to set email alerts
|

Errors, limitations, and pitfalls in the diagnosis of central and peripheral nervous system lesions in intraoperative cytology and frozen sections

Abstract: Context:Intraoperative cytology and frozen section play an important role in the diagnosis of neurosurgical specimens. There are limitations in both these procedures but understanding the errors and pitfalls may help in increasing the diagnostic yield.Aims:To find the diagnostic accuracy of intraoperative cytology and frozen section for central and peripheral nervous system (PNS) lesions and analyze the errors, pitfalls, and limitations in these procedures.Settings and Design:Eighty cases were included in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 14 publications
3
46
0
2
Order By: Relevance
“…The overall diagnostic agreement of SP with histology ranged from 83.7 to 97.6% (mean 91.7%) ( Table 3 ) . Only 6 studies cited sensitivities of 88.8% [4] , 94.3% [26] , 95.5% [25] , 96.0% [11] , 97.9% [13] , and 98.7% [22] , while 6 reported specificities of 75.0% [11] , 81.9% [4] , 87.5% [22] , 95.0% [13] , 95.6% [26] , and 100% [25] . The overall accuracy of SP/TP in our study, including both tumoral and nontumoral brain lesions, was similar to those found in the literature, with a sensitivity and specificity of 97.9 and 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall diagnostic agreement of SP with histology ranged from 83.7 to 97.6% (mean 91.7%) ( Table 3 ) . Only 6 studies cited sensitivities of 88.8% [4] , 94.3% [26] , 95.5% [25] , 96.0% [11] , 97.9% [13] , and 98.7% [22] , while 6 reported specificities of 75.0% [11] , 81.9% [4] , 87.5% [22] , 95.0% [13] , 95.6% [26] , and 100% [25] . The overall accuracy of SP/TP in our study, including both tumoral and nontumoral brain lesions, was similar to those found in the literature, with a sensitivity and specificity of 97.9 and 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…TP enables preservation of the cellular architecture and morphological features for subsequent histologic examination [5,11,24,27] , while avoiding the smearing or freezing artifacts of SP or FS [12,24,27] . The low cellular yield with TP can, however, lead to improper tumor grading or misdiagnoses [5,25,27] .…”
mentioning
confidence: 99%
“…An accurate diagnosis requires a good correlation between clinical data, imaging tests, and histopathological examination [1, 17, 18]. In our study, the resected specimens for intraoperative examination were not analyzed in the same facility of the surgical center; the imaging modalities are sometimes unavailable in the institution, and thus there is no direct contact with the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Most CNS lesions have a low amount of connective tissue, allowing adequate application of the squash technique, which provides more detailed information on cellular morphology than FS [1, 7, 8]. Meanwhile, FS is more applicable in cases in which performing the squash technique can be difficult, such as lesions that need better evaluation of the architectural aspects and those with firm consistency [6, 7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation